Factors related to first dose hypotensive effect of captopril: prediction and treatment. Issue 6368 (12th March 1983) - Hodsman, G P; Isles, C G; Murray, G D; Usherwood, T P; Webb, D J; Robertson, J I
Abstract : The blood pressure response to the first dose of captopril (6.25 mg, 12.5 mg, or 25 mg) was measured in 65 treated, severely hypertensive patients. Mean supine blood pressure was 187/108 mm Hg immediately before captopril was given. Twenty one patients experienced a fall in supine systolic pressure greater than 50 mm Hg, including five whose pressure fell more than 100 mm Hg and two whose pressure fell more than 150 mm Hg. Six patients developed symptoms of acute hypotension, including dizziness, stupor, dysphasia, and hemiparesis. Percentage reductions in blood pressure were greatest in those with secondary hypertension (p less than 0.05), high pretreatment blood pressure (p less than 0.05), and high concentrations of plasma renin and angiotensin II (p less than 0.01). No significant correlation was found between fall in blood pressure and serum sodium concentration, age, renal function, and the dose of captopril given. A severe first dose effect cannot be consistently predicted in individual patients who have received other antihypertensive drugs for severe hypertension. Such patients should have close medical supervision for at least three hours after the first dose of captopril.